Use of e-cigarette among Malaysian male adults: findings from global adult tobacco survey 2011 and national e-cigarette survey 2016 - Tee, Guat Hiong; Mohd Yusoff, Muhammad Fadhli; Wee, Lei Hum; Chan, Caryn Mei Hsien; Ab Rahman, Jamalludin; Ab Rahman, Norny Syafinaz; Draman, Samsul; Kartiwi, Mira; Omar, Mohd Azahadi; Ling, Jane Miaw Yn; Ho, Bee Kiau; Baharom, Nizam; et al. (Malaysian Medical Association (MMA), 2017)
Introduction: The use of electronic cigarettes (e-cigarettes) has become prevalent in many countries including Malaysia. Use of e-cigarettes has generated a lot of debates on its health effects and is a major public health concern. This study aimed to examine the use of e-cigarettes among Malaysian male adults aged 18 years and above in 2011 and 2016. Methods: Data were obtained from the Global Adult Tobacco Survey (GATS) 2011 and National E-Cigarette Survey (NECS) 2016. These were nationally representative household surveys using multi-stage cluster sampling design. Analyses were performed by using SPSS. Results: Overall prevalence of e-cigarette use among Malaysian adults aged 18 years and above were 0.9% (0.4-1.8) in 2011 and 2.8% (2.2-3.6) in 2016. E-cigarette use among male current smokers increased significantly from 3.5% (1.7-7.0) to 9.8% (7.5-12.8) in 2011 and 2016 respectively. E-cigarette use among male former smokers were 1.5% (0.2-10.2) in 2011 and 4.3 % (2.0-9.1) in 2016. The prevalence of e-cigarette use among male never smokers was 2.1% (1.2-3.5) in 2016. The three main reasons of e-cigarette use among male adults from NECS were: to experiment/try (47.0%; 95%CI: 38.1-56.0); to quit tobacco smoking (16.2%; 95%CI: 9.8-25.5); and to reduce tobacco smoking (9.6%; 95%CI: 4.6-18.9). Conclusions: The prevalence of e-cigarette use among male dual users aged 18 years and above increased significantly from 2011 to 2016. Surveillance in monitoring these dual users are needed. In addition, it is important to implement prevention control policies to protect never smokers from uptake of smoking through e-cigarettes. Further studies are warranted to justify the reasons for using e-cigarettes as claimed by this population.